1966
DOI: 10.1021/je60030a033
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Monoethanolamine Solutions in Carbon Dioxide Scrubbers.

Abstract: Monoethanolamine (MEA), the regenerative absorbent used in C02 scrubbers aboard nuclear submarines, is now stabilized with a chelating agent, the monosodium salt of , -diethanolglycine (VFS). This inhibitor is not effective against oxidative degradation at 55°C. in the presence of procatalytic metals, particularly copper. Effective stabilization in the presence of copper is given by tetrasodium (ethylenedinitrilo) tetraacetate (EDTA). At 98°C ., with small quantities of typical metal contaminants added, both V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…In this case, metals facilitate the propagation steps by catalyzing the generation of radicals from hydroperoxides as presented in Figure 1 15,16 . Hydroperoxides are generated by the presence of O 2 in water and their presence in oxidized MEA solutions has been evidenced previously 10 , which further supports this reaction pathway. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 Moreover, the presence of hydroperoxides is also due to the catalytic action of metals.…”
Section: Influence Of Dissolved Metals On Solvent Degradationsupporting
confidence: 81%
“…In this case, metals facilitate the propagation steps by catalyzing the generation of radicals from hydroperoxides as presented in Figure 1 15,16 . Hydroperoxides are generated by the presence of O 2 in water and their presence in oxidized MEA solutions has been evidenced previously 10 , which further supports this reaction pathway. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 Moreover, the presence of hydroperoxides is also due to the catalytic action of metals.…”
Section: Influence Of Dissolved Metals On Solvent Degradationsupporting
confidence: 81%
“…The catalytic effect of dissolved metals present in MEA solutions on the oxidative degradation rate has been reported [6]. In recent work, this effect was analyzed for the presence of ammonia as an indicator of MEA oxidative degradation.…”
Section: Accelerated Oxidative Degradation Testmentioning
confidence: 99%
“…Experiments from the 1960s, performed by the U.S. Department of the Navy, identified EDTA as an additive to stabilize MEA solutions to oxidative degradation. 10,42,43 These studies also identified bicine as a stabilizer, but it was much less effective. Previous studies in this research group confirmed these findings and found that EDTA was the most effective chelating agent for both Fe and Cu.…”
Section: O 2 Scavengers and Reaction Inhibitors Inhibitor Amentioning
confidence: 99%